Pengaruh Jenis Limbah Pertanian dan Konsentrasi EM4 terhadap Kandungan Unsur Hara Pupuk Organik Cair - WIDIADA, I MADE; KARTINI, NI LUH; WIJANA, GEDE (Agrotrop : Journal on Agriculture Science, 2022)
Effect of Agricultural Waste Types and Em4 Concentration on Nutrition Content of Liquid Organic Fertilizer.   Agricultural waste has not been used optimally. This waste can be used as liquid organic fertilizer to get healthy agricultural products and free of pesticide residues. The type of agricultural waste and the concentration of EM4 are factors that play a role in determining the nutrient content of liquid organic fertilizer. The purpose of this study was to obtain the type of agricultural waste, the concentration of EM4, and the best interaction with the nutrient content of liquid organic fertilizer. The research treatment consisted of two factors using a randomized block design. The first factor is the type of agricultural waste consists of three levels, namely (1) vegetable waste + pig waste, (2) vegetable waste + straw + pig waste, and (3) vegetable waste + straw + gamal leaves + pig waste. The second factor is the concentration of EM4 consists of three levels, namely the concentration of 5%, 10% and 15%. The results showed that there was a very significant interaction between types of agricultural waste with EM4 concentration on available P, organic C, pH, and total microbes with the best values of 333.38 ppm (very high), 1.95% (very low), 4.75 (acid), and 19.56 x 106 cfu ml-1. Vegetable waste + straw + gamal leaves + pig waste, and 10% EM4 concentration gave the best effect compared to other treatment combinations on nutrient content. It is recommended that to makes liquid organic fertilizer should use vegetable waste + straw + gamal leaves + pig waste with an EM4 concentration of 10%.